2020
DOI: 10.1186/s43044-020-00067-z
|View full text |Cite
|
Sign up to set email alerts
|

Estimated glomerular filtration rate as one of the main predictors of in-hospital mortality in Egyptian patients with ST elevation myocardial infarction: a two-year retrospective study

Abstract: Background: Renal dysfunction is one of the major causes of in-hospital mortality in STEMI patients. In this study, we evaluated the combined predictive value of eGFR by CKD-EPI equation and shock index for in-hospital mortality and other adverse clinical outcomes in Egyptian patients with STEMI. Results: A total of 450 STEMI patients were divided into 2 groups according to their eGFR with a cutoff value of 60 ml/min/1.73 m 2 and compared as regards mortality, major bleeding, reinfarction, development of heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
(30 reference statements)
0
7
1
1
Order By: Relevance
“…Previous studies have demonstrated prognostic value of renal function in patients with STEMI. [26][27][28] In present study, we found no significant impact of chronic renal dysfunction or creatinine on LOS. Interestingly, although numerous studies proved more advantages of transradial approach than transfemoral access in percutaneous coronary intervention (PCI), 29 even for STEMI patients with cardiogenic shock, 30 transradial approach was not an independent associated factor of LOS in this analysis.…”
Section: Discussioncontrasting
confidence: 56%
“…Previous studies have demonstrated prognostic value of renal function in patients with STEMI. [26][27][28] In present study, we found no significant impact of chronic renal dysfunction or creatinine on LOS. Interestingly, although numerous studies proved more advantages of transradial approach than transfemoral access in percutaneous coronary intervention (PCI), 29 even for STEMI patients with cardiogenic shock, 30 transradial approach was not an independent associated factor of LOS in this analysis.…”
Section: Discussioncontrasting
confidence: 56%
“…The proportion of underlying risk factors often increase along with declining GFR according to most prior studies, which was in agreement with our findings. 15–19 Thus, by shifting from normal toward severely decreased GFR, we observed a gradual increase in frequency of diabetes, former MI, prior cerebrovascular disease, hypertension, dyslipidemia, and advanced Killip class. Conversely, the male predominance decreases and the prevalence of current smoking falls as well.…”
Section: Discussionmentioning
confidence: 74%
“…Several studies have demonstrated a lower likelihood of in-hospital mortality in STEMI patients having normal renal function compared against those with decreased GFR, which is relatively close to our findings. 11,12, 15–19 These articles have categorized baseline GFR in agreement with our classification. However, some of them employed the MDRD equation 12,15,16 instead of the CKD-EPI, discussed here.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations